Influences of coal size, volatile matter content, and additive on primary particulate matter emissions from household stove combustion. (15th October 2016) - Li, Qing; Jiang, Jingkun; Zhang, Qi; Zhou, Wei; Cai, Siyi; Duan, Lei; Ge, Su; Hao, Jiming
Highlights: Incomplete combustion of coal volatile matter leads to significant PM emission from household stove. PM emission decrease with increasing coal size and mineral additive in household stove. Controlling coal properties helps to reduce PM emission from household coal combustion. Abstract: Aiming to reduce primary particulate matter (PM) emission from household coal combustion, we conducted experimental investigations on several coal properties that affect PM emission factors (EFs). Fourteen coal chunk samples with various volatile matter contents on dry and ash-free basis (Vdaf, 2.84–48.7%) were tested to examine the effect of coal volatile matter content. Eight coal briquette samples with various mineral additives were tested to examine the effect of coal additive. Two coal chunk samples with Vdaf of 32.9% and 9.3%, respectively, were made into three different sizes to examine the effect of coal size. Due to low combustion temperature and low burning efficiency of the volatile matter in household stoves, PMs emitted from household coal combustion often have a high fraction of carbonaceous compositions. Both PM2.5 EF and the fraction of its carbonaceous constituents increase with an increase in the coal volatile matter content till about Vdaf = 35% and then stay roughly flat. Addition of extraneous minerals results in a significant reduction of PM emissions. Increasing the coal size from ∼1 cm to ∼10 cm leads to a reduction of PM EFs by ∼80%. The coal volatile matter content determines the total amount of organic compounds to be devolatilized during coal pyrolysis stage. The coal size and ash content affect the escape of these organic compounds from burning coal chunks or briquettes. Together, they all affect the burning completeness of these organic compounds in household stoves and subsequently the total amount of organic precursors to form carbonaceous constituents in PMs.